Turning Point and Free Segments Strategies for Navigation of Wheeled Mobile Robot - Imen Hassani; Islem Ergui; Chokri Rekik (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The basic idea of the developed work is to solve the problem of mobile robot navigation with obstacle avoidance and the trajectory tracking problem in simple and complex environments. The research contribution aims to develop a strategy of navigation based on the turning point and the free segments algorithms. Indeed, a turning point method is developed in order to solve the problem of navigation in a simple environment. Then, the free segments approach is applied in order to solve the problem of obstacle avoidance in a complex environment. The second part of this paper aims to solve the problem of trajectory tracking. For this reason, a sliding mode controller is proposed as a solution to control the stability of the mobile robot. Finally, some simulation results which are developed using Matlab software are given to prove the validity of the developed work.